All Days 2012
DOI: 10.2118/159164-ms
|View full text |Cite
|
Sign up to set email alerts
|

First Horizontal-Well Production Logging and Water Control Success in a Tough Completion Offshore Well: A Case Study from China

Abstract: The Wen Chang oil field in the South China Sea is exploited mainly with horizontal wells completed with a sand screen and equipped with an electrical submersible pump (ESP) plus Y-tool for the production string. The water cut in one well has reached 74%, making diagnosis of the water entrance critical for a success remedial operation in the well. Because flow regimes in highly deviated and horizontal wells are quite different from those in vertical wells, the velocity and holdup distribution are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A semianalytical model is presented to estimate the locations of high-productive section based on the bottom-hole pressure data. 21,27 However, there are two issues not solved in the actual applications: (1) The effective producing length we obtained by current methods or softwares and our approaches 21,27 is less than the drilled or completed horizontal intervals. The misuses of the production rate distribution and horizontal well length would result in erroneous well and reservoir parameter interpretations.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A semianalytical model is presented to estimate the locations of high-productive section based on the bottom-hole pressure data. 21,27 However, there are two issues not solved in the actual applications: (1) The effective producing length we obtained by current methods or softwares and our approaches 21,27 is less than the drilled or completed horizontal intervals. The misuses of the production rate distribution and horizontal well length would result in erroneous well and reservoir parameter interpretations.…”
Section: Introductionmentioning
confidence: 94%
“…Al Rbeawi and Tiab 20 introduced the mathematical models to study the effects of multiple zonal isolations on pressure responses and concluded that the dominant effect of isolators can only be identified during the early radial or linear regimes. Cheng et al 21 developed a well-test model for the horizontal wells with nonuniform production rate considering the segmented oil production and various skin factors in different production segments by Green's function and Newman's product tool. Nie et al 22,23 established a semianalytical model for horizontal wells in a homogeneous, dual, and triple-porosity reservoir and then developed a time-tracking test method to reduce the well testing costs.…”
Section: Introductionmentioning
confidence: 99%
“…Aibazarov et al [20] described how to determine the downhole fluid flow path and further to optimize water shut-off operations by using integrating data from spectral noise logging tools and multisensor production logging. Over the past few years, many researchers pinpointed water entry intervals through production logging [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. On the other hand, another monitoring system can provide vital data (e.g., pressure and temperature) for waterinflux detection.…”
Section: Introductionmentioning
confidence: 99%